The Procedural Status of the Accused in the Pre-Trial Proceedings (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article analyzes coercive measures that can determine the procedural status of the accused in pre-trial proceedings, determine his rights and freedoms, impose duties, and be applied to the suspect by the investigator, inquirer and prosecutor. Also, in this regard, a scientific discussion is being introduced, taking into account the opinions of scientists from a number of national and foreign countries, and problems arising in practice are being studied. Also, on the basis of international legal standards, proposals and recommendations have been developed to improve the Criminal Procedure Code of the Republic of Uzbekistan.